The profile of deliberate self-poisoning cases presenting at the emergency department of Pelonomi Regional Hospital - Benedict, Matthew Olukayode Abiodun (My University, 2014)
Background Deliberate self-poisoning (DSP) remains a common method employed for suicide worldwide. Despite its frequent occurrence and the high cost required in its management, only few studies have been carried out on this subject in South Africa. Inadequate research into DSP in South Africa is a great concern as this may inadvertently result in an inadequate knowledge of health professionals on the general approach to victims presenting at emergency departments. This may consequently result in a poor clinical outcome of these cases. This study was aimed at determining the demographics of DSP cases presenting to the emergency department (ED) of Pelonomi hospital and also to enquire into the drugs/agents commonly used, reasons for DSP and the clinical outcome of these cases. Method This was a retrospective, descriptive study which was carried out by going through the hospital clinical records covering a period of eighteen months (1st January 2010 – 30th June 2011). The demographics and deliberate self-poisoning-related information were then collected, using a data collection form. The data was thereafter analysed by using descriptive statistics, calculated for continuous data. Frequencies and percentages were calculated for categorical data. Results Of the 212 DSP cases reviewed, 66% were female. Most patients (86.8%) were single and 65.6% were unemployed. DSP occurred more in the age-group of 20-39 years (68.8%). Majority of the DSP cases (84.4%) occurred in areas associated with poor socio-economic status.Paracetamol was the drug used by majority of these patients (21.7%) for DSP. Other common agents/drugs used were antidepressants (9.4%), antiretrovirals (ARVs) (9.9%) and household chemicals (19.3%). 85 patients (40.1%) took more than one drug/agent. Out of the 81 patients who had the reason for their poisoning stated, 40 patients had relationship disharmony (32 unmarried, 8 married). 15 patients had family issues which mainly resulted from conflicts with parents and grandparents. The medical reasons found amongst 5 patients were HIV infection, cancer and dental problems. Unemployment and post traumatic stress disorder following rape were the other reasons for DSP. The psychosocial problems of 10 patients were not specified. Majority of the patients (59.9%) were discharged in stable conditions. Low GCS (≤8) and hypothermia were common clinical features occurring amongst patients that got admitted. Conclusion DSP is still a common phenomenon, majorly amongst females in the age-group of 20-39 years, with poor quality of life. Relationship disharmony is the most common reason for poisoning. Drug/agents used can only be curtailed to a minimal extent. Prevention through early detection of vulnerable patients and early psychological management should be our goal.
Submitted in partial fulfillment of the requirement for the degree Master of Science in Emergency Medicine in the Faculty of Health Sciences at the University of Witwatersrand , July 2013
Keywords: Poisoning; Emergencies; Suicide, Attempted--statistics & numerical data